Impact of Face Masks on Female Body Perception is Modulated by Facial Expressions. (January 2022) - Mills, Eleanor; Guo, Kun
People routinely wear face masks during the pandemic, but little is known about their impact on body perception. In this online study, we presented female body images of Caucasian avatars in common dress sizes displaying happy, angry, and neutral facial expressions with and without face masks, and asked women to rate the perceived body attractiveness and body size. In comparison with mask-off condition, mask-on decreased body attractiveness ratings for happy avatars but did not affect ratings for neutral avatars irrespective of avatar dress sizes. For avatars displaying angry expressions, mask-on increased body attractiveness ratings for slimmer avatars but did not affect ratings for larger avatars. On the other hand, body size estimation was not systematically affected by face masks and facial expressions. It appears that face masks mainly show an expression-dependent influence on body attractiveness judgement, possibly through suppressing the perceived facial expressions.